A global analysis of song frequency in passerines provides no support for the acoustic adaptation hypothesis but suggests a role for sexual selection. (12th December 2020) - Mikula, Peter; Valcu, Mihai; Brumm, Henrik; Bulla, Martin; Forstmeier, Wolfgang; Petrusková, Tereza; Kempenaers, Bart; Albrecht, Tomáš
Abstract: Animals use acoustic signals for communication, implying that the properties of these signals can be under strong selection. The acoustic adaptation hypothesis predicts that species in dense habitats emit lower‐frequency sounds than those in open areas because low‐frequency sounds propagate further in dense vegetation than high‐frequency sounds. Signal frequency may also be under sexual selection because it correlates with body size and lower‐frequency sounds are perceived as more intimidating. Here, we evaluate these hypotheses by analysing variation in peak song frequency across 5, 085 passerine species (Passeriformes). A phylogenetically informed analysis revealed that song frequency decreases with increasing body mass and with male‐biased sexual size dimorphism. However, we found no support for the predicted relationship between frequency and habitat. Our results suggest that the global variation in passerine song frequency is mostly driven by natural and sexual selection causing evolutionary shifts in body size rather than by habitat‐related selection on sound propagation. Abstract : The acoustic adaptation hypothesis predicts that species in dense habitats emit lower‐frequency sounds than those in open areas because low‐frequency sounds propagate further in dense vegetation than high‐frequency sounds. We evaluated this hypothesis by analysing variation in peak song frequency across 5, 085 passerine species (Passeriformes) and found that song frequency decreased with increasing body mass and with male‐biased sexual size dimorphism. However, we found no support for the predicted relationship between song frequency and habitat.